2018
DOI: 10.1071/an15883
|View full text |Cite
|
Sign up to set email alerts
|

Asparagopsis taxiformis decreases enteric methane production from sheep

Abstract: Asparagopsis taxiformis concentrates halogenated compounds that are known to inhibit cobamide-dependent methanogenesis in vitro and, therefore, has potential to mitigate enteric methane production. The present study investigated the effect of Asparagopsis on methane (CH4) production from sheep offered a high-fibre pelleted diet (offered at 1.2 × maintenance) at five inclusion levels of Asparagopsis for 72 days (0% (control), 0.5%, 1%, 2% and 3% organic matter basis as offered). Individual animal CH4 measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
113
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(150 citation statements)
references
References 17 publications
10
113
0
Order By: Relevance
“…A significant reduction in CH 4 production was found when evaluating the effects of A. taxiformis on ruminal fermentation characteristics in-vitro at a 5% OM inclusion rate. Results from the overall experiment show an approximate decrease in TGP by ~50% and in CH 4 production by ~95%, which is similar to the reduction that was reported previously when the effect of A. taxiformis on CH 4 production from beef cattle was investigated [10,18,30] Carbon dioxide production remained similar between the control and A. taxiformis amended vessels. Comparison of total and individual VFA between vessels did not suggest any difference in VFA production at any specific time point with the 5% OM inclusion rate.…”
Section: Discussionsupporting
confidence: 85%
“…A significant reduction in CH 4 production was found when evaluating the effects of A. taxiformis on ruminal fermentation characteristics in-vitro at a 5% OM inclusion rate. Results from the overall experiment show an approximate decrease in TGP by ~50% and in CH 4 production by ~95%, which is similar to the reduction that was reported previously when the effect of A. taxiformis on CH 4 production from beef cattle was investigated [10,18,30] Carbon dioxide production remained similar between the control and A. taxiformis amended vessels. Comparison of total and individual VFA between vessels did not suggest any difference in VFA production at any specific time point with the 5% OM inclusion rate.…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, in vivo predicted CH 4 production was inhibited almost completely by AT already at a level of 0.5% on an OM basis. Li et al [45] added AT to diets fed to sheep and observed a reduction of CH 4 production at inclusion levels exceeding 1% of OM intake, but with altered rumen fermentation at all inclusion rates, i.e., at inclusions ≥0.5% of OM intake. On the other hand, in a short-term in vivo experiment by Stefenoni et al [46], inclusion of AT at 0.5% of DM intake decreased CH 4 emission in lactating dairy cows by 80%, with no negative effects on DM intake and milk yield (rumen fermentation parameters were not measured).…”
Section: Dietary Strategies To Decrease Ch 4 Production From Ruminantsmentioning
confidence: 99%
“…Methane measurements were taken using seven open circuit respiration chambers as described by Li et al (2016a). CH 4 recovery was made for individual chambers prior to chamber measurement following the procedure of Klein and Wright (2006).…”
Section: Enteric Methane Measurementmentioning
confidence: 99%